Code-switching as a communicative strategy among Malay students learning japanese in Malaysia Higher Education Institution - Abdullah, Muhammad Alif Redzuan; Hussin, Sanimah (Human Resource Management Academic Research Society, 2021)
Code-switching is an effective communicative strategy in learning Japanese as a foreign language in Malaysia Higher Education Institution. The tendency in code-switching is a common practice while communicating among the bilingual and multilingual Malaysian society. Furthermore, the setting of Malaysia is a perfect example where code-switching is a common phenomenon among its people, due to its multilingual and diversified cultural communities. This study aims to identify and analyse code-switching as a communicative strategy among ten Malay students who learn the Japanese language as a foreign language at MARA-OISCA Japanese Language Centre in Beranang, Malaysia. The theoretical frameworks adopted in the study used Hymes's internal code-switching and external code-switching framework model to discuss the types of code-switching patterns in analysing the data. The data were collected through pair discussion activities, recorded observation, and interviews. The findings revealed that participants used more internal code-switching compared to external code-switching. The findings also show that among the reasons that prompt Malaysian Japanese language learners in code-switching were four factors that can be resolved as the origin of the occurrence of code-switching, namely the social hierarchy, the relationship between speakers, lack of vocabulary knowledge and clear clarification of intended information. In addition, it was found that most Malaysian Japanese language learners use code-switching frequently and subconsciously.